Uma aplicação de metaheurísticas na abordagem do problema de layout de armazém - Davi, André da Silva (Universidade do Vale do Rio dos Sinos, 2017)
In this work a computational model was developed for a warehouse layout optimization. In addition to the Warehouse Layout Problem approach, the Part Family Problem is also addressed. For the development of the model was applied the metaheuristic Genetic Algorithm. The objective of the study is to design the configuration of a warehouse that optimizes an allocation of goods on the shelves that provides a minimization of the warehouse's movement during order selection, operation and management with essential uses of the operations and services performed. The decision variables are: the absolute distance of the location of the merchandise and the number of requests per day. The result is a set of new layouts, according to the conditions of service and the realization of an optimization of approximately 15%.
Keywords: Algoritmo genético; Centro de distribuição; Metaheurísticas; Layout de armazém; Genetic algorithm; Distribution center; Metaheuristics; Warehouse layout; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação